Bent out of shape: The impact of deviating heart morphology on cardiac function in Atlantic salmon (Salmo salar L.) - Victoria Becker; Simona Kavaliauskiene; Daniel Morgenroth; Sudip Mahat; William E. Louch; Ida B. Johansen; Michael Frisk (Aquaculture, 2026)

The influence of egg incubation and rearing temperature on heart morphology and function in farmed Atlantic salmon (Salmo salar) - Pia Skovholt Halvorsen; Sudip Mahat; Simen W. Larsen; Tuva M.G. Sørgaard; Victoria Becker; Daniel Morgenroth; Morten Strøm; Marit Stormoen; William E. Louch; Simona Kavaliauskiene; Ida B. Johansen; Michael Frisk (Aquaculture, 2026)

Functional and structural cardiac remodelling in farmed Atlantic salmon (Salmo salar) - Pia Skovholt Halvorsen; Sudip Mahat; Victoria Becker; Simona Kavaliauskiene; Tuva M.G. Sørgaard; Daniel Morgenroth; Morten Strøm; William E. Louch; Ida B. Johansen; Michael Frisk (Aquaculture, 2026)

Echocardiography - a non-invasive alternative for assessing cardiac morphology and function in Atlantic salmon (Salmo salar L.) - Victoria Becker; Simona Kavaliauskiene; Erik Sandblom; Lucas A. Zena; Albin Gräns; William E. Louch; Ivar Sjaastad; Ida B. Johansen; Michael Frisk (Aquaculture, 2024)

Leaf Shelters Facilitate the Colonisation of Arthropods and Enhance Microbial Diversity on Plants - Danilo F. B. dos Santos; Jacob E. Herschberger; Bijay Subedi; Victoria M. Pocius; Wesley J. Neely; Sasha E. Greenspan; C. Guilherme Becker; Gustavo Q. Romero; Mônica F. Kersch‐Becker (Ecology Letters, 2024)
Shelter‐building insects are important ecosystem engineers, playing critical roles in structuring arthropod communities. Nonetheless, the influence of leaf shelters and arthropods on plant–associated microbiota remains largely unexplored. Arthropods that visit or inhabit plants can contribute to the leaf microbial community, resulting in significant changes in plant–microbe interactions. By artificially constructing leaf shelters, we provide evidence that shelter‐building insects influence not only the arthropod community structure but also impact the phyllosphere microbiota. Leaf shelters exhibited higher abundance and richness of arthropods, changing the associated arthropod community composition. These shelters also altered the composition and community structure of phyllosphere microbiota, promoting greater richness and diversity of bacteria at the phyllosphere. In leaf shelters, microbial diversity positively correlated with the richness and diversity of herbivores. These findings demonstrate the critical role of leaf shelters in structuring both arthropod and microbial communities through altered microhabitats and species interactions.

Utilization of treated wastewater derived from microalgae production for the irrigation of horticultural crops - Alejandro Rápalo-Cruz; Cintia Gómez-Serrano; Cynthia Victoria González-López; Ainoa Morillas-España; Silvia Jiménez-Becker (Journal of Applied Phycology, 2024)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Climate variability and aridity modulate the role of leaf shelters for arthropods: A global experiment - Gustavo Q. Romero; Thiago Gonçalves‐Souza; Tomas Roslin; Robert J. Marquis; Nicholas A.C. Marino; Vojtech Novotny; Tatiana Cornelissen; Jerome Orivel; Shen Sui; Gustavo Aires; Reuber Antoniazzi; Wesley Dáttilo; et al. (Global Change Biology, 2022)
Current climate change is disrupting biotic interactions and eroding biodiversity worldwide. However, species sensitive to aridity, high temperatures, and climate variability might find shelter in microclimatic refuges, such as leaf rolls built by arthropods. To explore how the importance of leaf shelters for terrestrial arthropods changes with latitude, elevation, and climate, we conducted a distributed experiment comparing arthropods in leaf rolls versus control leaves across 52 sites along an 11,790 km latitudinal gradient. We then probed the impact of short‐ versus long‐term climatic impacts on roll use, by comparing the relative impact of conditions during the experiment versus average, baseline conditions at the site. Leaf shelters supported larger organisms and higher arthropod biomass and species diversity than non‐rolled control leaves. However, the magnitude of the leaf rolls’ effect differed between long‐ and short‐term climate conditions, metrics (species richness, biomass, and body size), and trophic groups (predators vs. herbivores). The effect of leaf rolls on predator richness was influenced only by baseline climate, increasing in magnitude in regions experiencing increased long‐term aridity, regardless of latitude, elevation, and weather during the experiment. This suggests that shelter use by predators may be innate, and thus, driven by natural selection. In contrast, the effect of leaf rolls on predator biomass and predator body size decreased with increasing temperature, and increased with increasing precipitation, respectively, during the experiment. The magnitude of shelter usage by herbivores increased with the abundance of predators and decreased with increasing temperature during the experiment. Taken together, these results highlight that leaf roll use may have both proximal and ultimate causes. Projected increases in climate variability and aridity are, therefore, likely to increase the importance of biotic refugia in mitigating the effects of climate change on species persistence.

Subtle structures with not‐so‐subtle functions: A data set of arthropod constructs and their host plants - Cássio Cardoso Pereira; Samuel Novais; Milton Barbosa; Daniel Negreiros; Thiago Gonçalves‐Souza; Tomas Roslin; Robert Marquis; Nicholas Marino; Vojtech Novotny; Jerome Orivel; Shen Sui; Gustavo Aires; et al. (Ecology, 2022)
The construction of shelters on plants by arthropods might influence other organisms via changes in colonization, community richness, species composition, and functionality. Arthropods, including beetles, caterpillars, sawflies, spiders, and wasps often interact with host plants via the construction of shelters, building a variety of structures such as leaf ties, tents, rolls, and bags; leaf and stem galls, and hollowed out stems. Such constructs might have both an adaptive value in terms of protection (i.e., serve as shelters) but may also exert a strong influence on terrestrial community diversity in the engineered and neighboring hosts via colonization by secondary occupants. Although different traits of the host plant (e.g., physical, chemical, and architectural features) may affect the potential for ecosystem engineering by insects, such effects have been, to a certain degree, overlooked. Further analyses of how plant traits affect the occurrence of shelters may therefore enrich our understanding of the organizing principles of plant‐based communities. This data set includes more than 1000 unique records of ecosystem engineering by arthropods, in the form of structures built on plants. All records have been published in the literature, and span both natural structures (91% of the records) and structures artificially created by researchers (9% of the records). The data were gathered between 1932 and 2021, across more than 50 countries and several ecosystems, ranging from polar to tropical zones. In addition to data on host plants and engineers, we aggregated data on the type of constructs and the identity of inquilines using these structures. This data set highlights the importance of these subtle structures for the organization of terrestrial arthropod communities, enabling hypotheses testing in ecological studies addressing ecosystem engineering and facilitation mediated by constructs. There are no copyright restrictions and please cite this paper when using the data in publications.

Cortical brain atrophy and intra-individual variability in neuropsychological test performance in HIV disease - Lindsay J. Hines; Eric N. Miller; Charles H. Hinkin; Jeffery R. Alger; Peter Barker; Karl Goodkin; Eileen M. Martin; Victoria Maruca; Ann Ragin; Ned Sacktor; Joanne Sanders; Ola Selnes; et al. (Brain Imaging and Behavior, 2016)

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for natural variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; Sven Enterlein; et al. (Archives of Virology, 2013)

Subcortical brain atrophy persists even in HAART-regulated HIV disease - James T. Becker; Joanne Sanders; Sarah K. Madsen; Ann Ragin; Lawrence Kingsley; Victoria Maruca; Bruce Cohen; Karl Goodkin; Eileen Martin; Eric N. Miller; Ned Sacktor; Jeffery R. Alger; et al. (Brain Imaging and Behavior, 2011)